2018
DOI: 10.1007/s12094-018-1888-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-surgical trial of the AKT inhibitor MK-2206 in patients with operable invasive breast cancer: a New York Cancer Consortium trial

Abstract: While a trend to pAKT reduction after MK-2206 was observed, there was no significant change compared to controls. However, the accrued population was limited, due to toxicity being greater than expected. Pre-surgical trials can identify in vivo activity in the early drug development, but side effects must be considered in this healthy population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…In our preclinical work, we had shown that MK-2206 led to a dose-dependent decrease in AKT signaling in vitro and a dose-dependent decrease in tumor growth in vivo, with regression observed at higher doses that were associated with decreases in AKT signaling. These results are in line with a recent report from Kalinsky et al where they assessed MK-2206 pharmacodynamics effect in a presurgical window-of-opportunity trial in breast cancer [15]. Two doses of MK-2206 were administered, 9 and 2 days before surgery.…”
Section: Discussionsupporting
confidence: 87%
“…In our preclinical work, we had shown that MK-2206 led to a dose-dependent decrease in AKT signaling in vitro and a dose-dependent decrease in tumor growth in vivo, with regression observed at higher doses that were associated with decreases in AKT signaling. These results are in line with a recent report from Kalinsky et al where they assessed MK-2206 pharmacodynamics effect in a presurgical window-of-opportunity trial in breast cancer [15]. Two doses of MK-2206 were administered, 9 and 2 days before surgery.…”
Section: Discussionsupporting
confidence: 87%
“…PI3K/AKT/mTOR and CDK4/6 inhibitors are emerging drugs for the treatment of ER-positive and human epidermal growth factor receptor-2 (HER2) negative metastatic BC ( 95 ). The PI3K/AKT/mTOR pathway is an important oncogenic signaling pathway in BC that can be activated by hyperglycemia to promote the proliferation of malignant BC epithelial cells ( 56 , 95 ). Everolimus is an mTOR inhibitor that can target the rapamycin pathway.…”
Section: Hyperglycemia Affects Response To Therapy In Bc Patientsmentioning
confidence: 99%
“…Likewise, completion of the trial testing MK-2206 plus anti-estrogen therapy for ER pos breast cancer failed to show clinical activity above that of anastrazole alone [38]. Finally, a trial using MK-2206 as a monotherapy prior to scheduled surgical resection of operable breast cancer was stopped due to unexpectedly high toxicity, given this particular clinical setting [39]. It therefore appears that MK-2206, like other Akt inhibitors currently being tested, are of unproven value therapeutically, at least as part of the therapy regimens tested up to this point.…”
Section: Discussionmentioning
confidence: 99%